THE BOUCHARD-TAYLOR COMMISSION (Andamios, Revista de Investigación Social, 2009)
In February 2007, Québec Premier set up a Commission which was given the task of asking citizens about reasonable accommodation practices related to cultural differences. These practices have deeply marked the political and social life of Quebecers the last few years. This article analyzes the Bouchard-Taylor Commission’s work, especially the wide public consultation which was developed in a public debate, giving rise to an intensive participative and deliberative practice without precedent in that nation’s history.
Keywords: Participative democracy; public consultation; reasonable accommodations; intercultural harmonization; Québec